2006
DOI: 10.1158/0008-5472.can-05-2828
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of the HOXA10 Homeobox Gene in Endometrial Carcinoma: Role in Epithelial-Mesenchymal Transition

Abstract: Homeobox genes encode transcription factors that control cell differentiation and play essential roles in developmental patterning. Increasing evidence indicates that many homeobox genes are aberrantly expressed in cancers, and that their deregulation significantly contributes to tumor progression. The homeobox gene HOXA10 controls uterine organogenesis during embryonic development and functional endometrial differentiation in the adult. We investigated whether HOXA10 expression is deregulated in endometrial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
98
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 42 publications
6
98
0
8
Order By: Relevance
“…41 Recently, several transcription factors that are molecular mediators of epithelial-to-mesenchymal transition, such as Twist, ZEB1, and HOXA10, have been shown to be expressed in endometrial carcinoma. 8,42,43 Of particular interest is that ZEB1 has an expression pattern in endometrial carcinoma quite similar to that for S100A4. None of these transcription factors has been shown previously to directly regulate S100A4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…41 Recently, several transcription factors that are molecular mediators of epithelial-to-mesenchymal transition, such as Twist, ZEB1, and HOXA10, have been shown to be expressed in endometrial carcinoma. 8,42,43 Of particular interest is that ZEB1 has an expression pattern in endometrial carcinoma quite similar to that for S100A4. None of these transcription factors has been shown previously to directly regulate S100A4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Common genetic abnormalities in EC include mutations in PTEN, K-RAS, PI3CA and CTNNB1; TP53 mutations are very rare (Prat et al, 2007). Epigenetic studies have linked hypermethylation to the loss of expression of DNA repair enzymes, MLH1 and O6-methylguanine DNA methyltransferase (MGMT), the tumor suppressors, PTEN, p53 and TIG1, the progesterone receptor, the b-catenin/Wnt signaling regulator, APC (adenomatous polyposis coli), the transcription factor, C/EBPa, and the differentiation gene, HoxA10 (Furlan et al, 2006;Shang, 2006;Yoshida et al, 2006;Zhou et al, 2007). Alternatively, hypomethylation has been described as a contributing factor for oncogene overexpression in EC.…”
mentioning
confidence: 99%
“…The role of HOXA10 in human endometrial epithelial cells is unclear. Studies have demonstrated that the expression of HOXA10 in endometrial adenocarcinoma, which arises from the glandular epithelium, is either increased (Lane et al, 2004) or decreased (Yoshida et al, 2006) compared with normal endometrium. Thus, it remains uncertain as to the role of HOXA10 in endometrial adenocarcinoma or in normal epithelial cell differentation.…”
Section: Discussionmentioning
confidence: 99%